A Project Feasibility Study on MILCOCO - Gutano, Georgina D.; Pendel, Vivien I.; Perez, Diane M.; Sanchez, Richard C. (College of Engineering, 2002)
Philippines have a high dependency on developed countries as its source of dairy products. Statistics gathered from the National Dairy Authority reveals the insufficiency of local milk production to provide for the milk consumption requirement of the population. Aiming to reduce the dependency on milk importation, various technologies have been developed to produce modified milk products out of cheaper blend of coconut. In line with this, the company conducted a study on the feasibility of cultured milk made from coconut milk branded as Milcoco. The company initially conducted a market study to determine the demand for the nature and behavior of the market for cultured milk drinks. Te study was also carried out to determine the consumer acceptability of Milcoco. Results of the market study revealed unsatisfied demands for cultured milk drinks. The demand-supply gaps determined for the project period were 38,880,753; 36,490,772; 34,095,625; and 29,292,567 respectively. However, the company decided to capture only a portion of the demand gaps of the project periods. The company aims to target the above the poverty-line population of the NCR market. NCT was chosen over the other regions primarily due to its highly populated areas. The market shares determined through analysis of the consumer survey results fir 2003, 2004, and 2005-2007 15.15%, 19.17% and 20.98% respectively. Various marketing strategies, such as sales promotions and advertisements were formulated to ensure the successful entry of Milcoco products in the NCR market. After establishing the market viability of Milcoco, the company conducted a technical study to determine the available technological alternatives that may be used to establish the manufacturing process plan for the production of Milcoco. The company decided to use coconut milk powder over the liquid coconut milk due to lack of available suppliers of bulk amounts of coconut milk. Based on the demand volumes of Milcoco the company decided to operate at 240 working days, with 2 batch productions from Mondays to Thursday. Evaluations of material suppliers were conducted. Availability of local suppliers further suggests the technical viability of the project venture. This ensured that sufficient amount of raw and packaging materials are available to meet the requirements of the company. The layout of the manufacturing plant was designed to meet the space requirements of the various activity centers of the company. A comparative analysis of various potential site locations was made to determine the most ideal plant site. After considering various plant site alternatives, the company decided to locate its plant at Victoria Wave Special Economic Zone, located in Malaria Tala, Kalookan City. The investment and capital expenditures of the project venture were determined. The total project cost was estimated at Php 90,000,000. A corporate organization will be formed to carry out the functions of the company. Financial measures were computed based on the figures obtained from the Income, cash flow and balance sheet projections. Based on the measures computed, the company was found to be capable of meeting short-term obligations and remain to be liquid within the projected period of operation. Overall, the project venture is feasible due the availability of appropriate materials and equipment necessary for the production of Milcoco. Furthermore, the project yields benefits to the society in terms of the additions to government revenues through tax contributions, employment of workers and generation of revenues for local suppliers. The venture will also provide alternative sources.